PELATIHAN MEMBUAT KREASI PIZZA DENGAN VARIAN KHAS NUSANTARA KEPADA SMK PARIWISATA GEMA GAWITA - Juliana; Ira B Hubner; Edwan Tanyauw; Emmanuel Fernando; Steven Elroy (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
kemasan, pizza , cita rasa varian nusantara, ayam sambal matah, entrepreneur Abstract: Community service is an activity carried out for the practice of science, technology and culture with the aim of providing insight and also improving and developing community capabilities. The purpose of this community service activity is to socialize and provide training to Gema Gawita Tourism Vocational School students on how to make pizza with a typical Indonesian variant, namely chicken chili matah. To provide guidelines on how to make good and attractive pizza packaging/packaging to be marketed. The Community Service Team will create an online video/workshop for SMIP Gema Gawita Tourism Vocational School students with the aim of being able to benefit local residents so that in the future they can become one of the livelihoods of residents there who want to start a business or become an entrepreneur